2021
DOI: 10.1002/hed.26814
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate dehydrogenase is a predictive biomarker in patients with oropharyngeal cancer undergoing radiotherapy: Retrospective study on predictive factors

Abstract: Background The present study aimed to evaluate the prognostic factors in human papillomavirus (HPV)‐positive and HPV‐negative oropharyngeal cancer (OPC) treated with definitive radiotherapy. Methods We retrospectively evaluated 101 patients with OPC who underwent definitive radiotherapy between 2008 and 2018. Results The median follow‐up period of the surviving patients was 68 months (range, 8–164 months). The 5‐year overall survival rate was 69.8%. Univariate analyses revealed that poor survival was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“… 23 , 24 More limited studies have found LDH to have prognostic significance in head and neck cancers as well. 25 , 26 , 27 , 28 LDH is a key enzyme in anaerobic glycolysis through conversion of pyruvate to lactate and is thought to reflect more aggressive cancers, which are able to proliferate under hypoxic conditions. 25 , 29 Hypoxic tumor conditions are well‐known to lead to resistance to radiation and chemotherapy, indicating that elevated LDH may be an indirect marker of resistance to these treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 , 24 More limited studies have found LDH to have prognostic significance in head and neck cancers as well. 25 , 26 , 27 , 28 LDH is a key enzyme in anaerobic glycolysis through conversion of pyruvate to lactate and is thought to reflect more aggressive cancers, which are able to proliferate under hypoxic conditions. 25 , 29 Hypoxic tumor conditions are well‐known to lead to resistance to radiation and chemotherapy, indicating that elevated LDH may be an indirect marker of resistance to these treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 , 27 , 28 LDH is a key enzyme in anaerobic glycolysis through conversion of pyruvate to lactate and is thought to reflect more aggressive cancers, which are able to proliferate under hypoxic conditions. 25 , 29 Hypoxic tumor conditions are well‐known to lead to resistance to radiation and chemotherapy, indicating that elevated LDH may be an indirect marker of resistance to these treatment modalities. 30 Our novel findings suggest that elevated serum LDH may also represent resistance to ICIs as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cancer cells that survived in a TME of intermittently hypoxia and starvation, glucose metabolism transforms to glycolysis even in an aerobic environment is ubiquitous ( 5 , 12 ). Metabolites produced by glycolysis support the excessive proliferation and metastasis of cancer cells, such as secreted lactate creates an acidic microenvironment which promoted cancer cells invasion abilities and absconding from chemotherapy ( 13 , 14 ). Therefore, aberrantly elevated glycolysis in cancer cells was thought to be closely related to poor prognosis in malignancies, including ccRCC ( 6 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have hypothesized that the metabolic cause of elevated LDH levels in patients with poorer outcomes is related to the presence of increased hypoxia due to the enzyme's function in anaerobic conditions. 34 , 36 …”
Section: Discussionmentioning
confidence: 99%